Magnetic interplay between two different lanthanides in a tris-phthalocyaninato complex: a viable synthetic route and detailed investigation in the bulk and on the surface. Issue 38 (29th July 2015) - Lan, Yanhua; Klyatskaya, Svetlana; Ruben, Mario; Fuhr, Olaf; Wernsdorfer, Wolfgang; Candini, Andrea; Corradini, Valdis; Lodi Rizzini, Alberto; del Pennino, Umberto; Troiani, Filippo; Joly, Loïc; Klar, David; et al.
Abstract : Future applications of molecular units in quantum information technologies require a fine control at the single molecule level. Abstract : Future applications of molecular units in quantum information technologies require a fine control at the single molecule level. This includes the choice of each functional element, the intramolecular interaction and the robustness of molecules when dispersed on a substrate. Keeping these goals in mind, we designed and synthesized a heterometallic phthalocyaninato-complex including two different lanthanides in each moiety, namely [PcDyPcTbPc*] (Pc being phthalocyanines; and Pc* being 2, 3, 9, 10, 16, 17, 23, 24-octahexyl-substituted phthalocyanines). Full magnetic characterization was performed down to the mK temperature range on bulk microcrystals by means of AC susceptibility, DC magnetization (including microSQUID) and specific heat measurements. A weak, yet sizeable, interaction between the two lanthanides is clearly detected by different techniques, altering the magnetic behavior of the single lanthanide as observed in the parent [LnPc2 ] complexes. Isolated [PcDyPcTbPc*] molecules dispersed on HOPG and the Au surface by liquid phase deposition are proven to maintain their main chemical and magnetic features by combined XPS, XAS and XMCD analysis and to lie with one Pc ligand flat to the surface. Opening of a small but sizable hysteresis loop at 1.8 K is directly observed on both Tb and Dy sites proving the retention of magnetization at the single molecule level.